Arts & humanities through the eras - Bleiberg, Edward I. (Gale virtual reference library, 2005)
Profiling milestones and movements in the arts, literature, music and religion from a specific period, each volume in this set helps students and researchers understand the various disciplines of the humanities in relation to each other, as well as to history and culture. An overview of the period and a chronology of major world events begin each volume.